Analisis Kesesuaian Judul Dan Isi Pada Puisi Karangan Siswa Kelas VII SMP Negeri 1 Bangsalsari - Cicin Dwi Quraini; Mohamad Afrizal; Yerry Mijianti (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Poetry is a form of a variety of literature and language that is bound by rhythm, meter, rhyme, as well as the arrangement of lines and stanzas, and based on its types, poetry has several types of narrative, lyric, and descriptive. The relationship between types of poetry and writing poetry is that poetry is a literary work that contains the poet's responses and opinions about various things. Students prefer to rewrite poetry that has been presented in books, so research on the suitability of the title and content needs to be carried out to develop students' abilities. The poems written by students in this research were poetry compositions that they wrote themselves. What is related to cohesion in student poetry starts from diction. Choosing the right and appropriate words to express an idea or thought. Poetry is the result of a poet's interpretation of life. This is how. Using Indonesian, the words literature, susastra, literature and literature have different meanings. The word literature used to be written as literature, but as language developed it was later written as literature. The word literature comes from Sanskrit, namely from the root word cas and the addition -tra. The word cas means 'to teach', while the suffix -tra means 'tool'. So, castra means 'tool for teaching'.